In any ΔABC, prove that


In any ΔABC, prove that

$a c \cos B-b c \cos A=\left(a^{2}-b^{2}\right)$



Left hand side,

$a c \cos B-b c \cos A$

$=a c \frac{a^{2}+c^{2}-b^{2}}{2 a c}-b c \frac{b^{2}+c^{2}-a^{2}}{2 b c}\left[A s, \cos B=\frac{a^{2}+c^{2}-b^{2}}{2 a c} \& \cos A=\frac{b^{2}+c^{2}-a^{2}}{2 b c}\right]$





$=$ Right hand side. [Proved]


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now